Pelayanan Publik di Fakultas Ilmu Sosial dan Ilmu Politik Tahun 2015-2016 - Wan Asrida (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
Faculty of Social Science and Political Science is one of the faculties in Riau University as spearhead of higher education services. This faculty provide services both academic and non”academic in accordance with Standard Operating Procedures (SOP) have been established by University. Therefore, sustaining it requires an ethics in the public service to civitas academica. The problem formulation in this research is (1) How is the application of ethics public service in Faculty Social Science and Political Science year 2015-2016? (2) What is the impact application of ethics public service to the quality of public service in Faculty Social Science and Political Science year 2015- 2016?. This research to aim (1) To describe application of type public service in Faculty Social Science and Political Science year 2015 -2016 and (2) To analysis of quality public service to quality public service in Faculty Social Science and Political Science year 2015-2016. The results of research to show is the services provided by Faculty Social Science and Political Science is of administrative services, facilities and infrastructure. Then, in terms of quality of service provide has met the minimum service standard in accordance with guidelines or regulations of the rector on public service on campus to the civitas academica. Nonetheless, still many types of public service which should be improved example academic portal and facilities and infrastructure in lectures. Therefore, the faculty take a strategy to optimize expectations the civitas academica and utilization of information technology to overcome it.